RETROTEXT-E 2.0 maximising teachers’ professional development. - Universiti Putra Malaysia, Research Management Centre (Research Management Centre, Universiti Putra Malaysia, 2010)
RETROTEXT-E is a recent invention which attempts to benefit teachers as much as possible, perhaps to make their lives better. It is a tool for teachers to add more variety to their otherwise predictable life in schools. Most teachers teach and spend the rest of their day working on marking exercise books or doing administrative work. On-going evaluation of the materials that they use for teaching has probably never been a consideration. RETROTEXT-E is aimed to change all that. At present there are two ways in which books, especially for English Language Teaching (ELT) are evaluated, the first way is to evaluate them impressionistically, while the second is by using an instrument, commonly known as a textbook evaluation checklist. While ELT textbooks can be evaluated efficiently through impression by experienced teachers, this may not be the case for novice teachers. Besides that, if more than one teacher is involved, impressionistic evaluation may not be feasible. Most teachers would then resort to the checklist. Although there are numerous checklists developed throughout the world, most of them have been tested for neither reliability nor validity. Another important point to be made is that checklists have been known to have very little capability of helping teachers evaluate important aspects of textbooks, especially with regard to the evaluation of vocabulary and structures, hence the need for some form of assistance from computers.